An Intentional and Ethical Integration of AI In Medical Imaging. - Turpin, Dean (Radiologic Technology)
This article focuses on the intentional and ethical integration of artificial intelligence (AI) in medical imaging, emphasizing the evolving role of radiologic technologists as supervisors and ethical stewards of AI technologies. It outlines AI’s capabilities in enhancing diagnostic accuracy, workflow efficiency, quality assurance, and personalized patient care, while highlighting challenges related to clinical autonomy, ethical implementation, bias, patient consent, and cultural considerations. The report advocates for comprehensive education, transparent governance, and human-centered AI design to ensure that AI supports rather than replaces human judgment and compassion in health care. It also envisions future AI applications that augment radiologic practice through real-time protocol recommendations, multilingual communication, and continuous quality improvement, stressing the importance of maintaining professional accountability and patient dignity throughout AI adoption.